2014
DOI: 10.1186/1756-0381-7-8
|View full text |Cite
|
Sign up to set email alerts
|

A classification and characterization of two-locus, pure, strict, epistatic models for simulation and detection

Abstract: Background:The statistical genetics phenomenon of epistasis is widely acknowledged to confound disease etiology. In order to evaluate strategies for detecting these complex multi-locus disease associations, simulation studies are required. The development of the GAMETES software for the generation of complex genetic models, has provided the means to randomly generate an architecturally diverse population of epistatic models that are both pure and strict, i.e. all n loci, but no fewer, are predictive of phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This observation highlights the importance of considering gene-gene interaction in discovering the genetic architecture of quantitative traits, even when the loci do not show significant single locus effects (i.e. when the model is purely epistatic Urbanowicz et al, 2014). Using simulated regulatory networks, Gjuvsland et al (2007) have shown that statistical epistasis is generated by functionally-dependent genes and the amount of genetic variance explained by epistatic interaction depends on the sign of the feedback.…”
Section: Discussionmentioning
confidence: 88%
“…This observation highlights the importance of considering gene-gene interaction in discovering the genetic architecture of quantitative traits, even when the loci do not show significant single locus effects (i.e. when the model is purely epistatic Urbanowicz et al, 2014). Using simulated regulatory networks, Gjuvsland et al (2007) have shown that statistical epistasis is generated by functionally-dependent genes and the amount of genetic variance explained by epistatic interaction depends on the sign of the feedback.…”
Section: Discussionmentioning
confidence: 88%
“… 12 13 The latter is certainly a reasonable approach; however it will miss potential interactions which involve SNPs with no main effects (i.e. it will miss what is referred to as ‘pure and strict epistasis’ 14 ).…”
Section: Filters and Encodingsmentioning
confidence: 99%
“…Two of the 2-locus models are the models with marginal effects. Junghyun Namkung et al developed Models 1 (Table III) and 2 (Table IV) [14] by varying the strength of genetic effects while fixing the interaction structure, the minor allele frequency (MAF) and prevalence. Two of the 3-locus models are called XOR model [15] (Table V) and ZZ model [16], [17] (Table VI), respectively.…”
Section: ) Gametes Datasetsmentioning
confidence: 99%